Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2147/cia.s311081
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Upper Arm Circumference as an Alternative Screening Instrument to Appendicular Skeletal Muscle Mass Index for Diagnosing Sarcopenia

Abstract: Purpose Mid-upper arm circumference (MUAC) is a simple, noninvasive anthropometric indicator. This study evaluated the applicability of MUAC as an alternative screening instrument to appendicular skeletal muscle mass index (ASMI) for detecting sarcopenia, and determined the optimal MUAC cutoff values. Patients and Methods A total of 4509 subjects ≥50 years of age from the West China Health and Aging Trend study were included in the present study. ASM was measured by bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 37 publications
5
35
1
1
Order By: Relevance
“…Recently, a Chinese study reported that the optimal AC cutoff values for a low SMI based on AWGS2019 were 28.6 cm for men and 27.5 cm for women [ 14 ], which were higher than the values determined by our study. This may have been due to differences in the technique used for taking measurements: in the Chinese study, the measurement was performed with the dominant hand, whereas in the present study, the measurement was performed with the non-dominant hand.…”
Section: Discussioncontrasting
confidence: 82%
“…Recently, a Chinese study reported that the optimal AC cutoff values for a low SMI based on AWGS2019 were 28.6 cm for men and 27.5 cm for women [ 14 ], which were higher than the values determined by our study. This may have been due to differences in the technique used for taking measurements: in the Chinese study, the measurement was performed with the dominant hand, whereas in the present study, the measurement was performed with the non-dominant hand.…”
Section: Discussioncontrasting
confidence: 82%
“…MUAC is a representative and noninvasive indicator for subcutaneous fat in the upper body, which is often suggested as a novel predictor of nutritional status, central obesity, and insulin resistance (IR). [ 9 , 10 , 11 ] However, there are no published data to evaluate the association between MUAC and liver steatosis and fibrosis. In this study, we included 1640 participants with MAFLD and 757 participants with MAFLD combined with other chronic liver diseases from a national survey database.…”
Section: Introductionmentioning
confidence: 99%
“…However, both genders experienced the same decline in muscle mass with aging, which is noticeable after the fifth decade 9 . The literature has also reported gender-specific differences in mid-upper arm circumference 38 , calf circumference 39 , and ASMI 1 , 2 . These differences between genders are also reflected in the present study.…”
Section: Discussionmentioning
confidence: 98%